Incest Relationship between a Sister and Mentally Retarded Brother which Resulted in Pregnancy and Birth: A Case Report - Mustafa Dogan; Mucahit Oruc; Osman Celbis; Bora Ozdemir; Semih Petekkaya (Medicine Science, 2016)
Incest is an illegal sexual relationship which is encountered in all societies and more often seen in childhood with psychologically destructive effects. The incest is presented between an antaomically virgin girl who experienced sexual relations resulting pregnancy and birth, with her older brother who didnt have adequate sexual relationship information and thought he was playing games, re-enacting what seen on films and television. The girl 12 year-old at the time of incest, didnt realise that she was pregnant so the pregnancy couldn't be terminated and she gave birth to a baby. Applied tests, the accused brother was determined with mild mental retardation, but he had been educated to high school level. The girl was determined to have developed a severe mental disorder because of the event. In this case of incest which resulted in a birth, the girl was found to be victim, the sister and the infants mother and the boy with mental retardation was the perpetrator. Our aim was to draw attention to destructive effects within the family of incest. In addition, incest cases are rarely seen, it should be pointed out that besides the girl as victim, the mentally-retarded brother and the newborn infant were also victims. [Med-Science 2016; 5(2.000): 709-14]